Authority in Space?: Creating a Digital Web-based Map Archive - Withers, Charles W.J.; Grout, Andrew (Archivaria, 2006)
The paper discusses the creation between 1999 and 2002 of a collaborative Web-based digital image and map catalogue archive, “Charting the Nation,” coordinated by the Department of Geography, University of Edinburgh, and Edinburgh University Library. The creation of the archive, based on the maps, cataloguing information and associated manuscript sources in the holdings of numerous collaborating institutions, is examined in relation to questions concerning the nature of archives generally and to this archive in particular as a “space” of authority. Issues posed by the electronic archive as a “virtual space” and in the creation and practical management of this digital Web-based map archive are addressed in relation to debates on postmodernism and the archive and to geographical and other literature on the situated nature of knowledge. RÉSUMÉ Ce texte examine la création entre 1999 et 2002 de « Charting the Nation », une collection d’archives Web en commun qui comprend des images numérisées et un catalogue cartographique, qui ont été coordonnés par le Département de géographie de l’Université d’Édimbourg et la Bibliothèque de l’Université d’Édimbourg. La création de ces archives, basée sur des documents cartographiques, de l’information de catalogage et des sources manuscrites associées provenant de plusieurs institutions en collaboration, est examinée en relation aux questions entourant la nature même des archives de façon générale et la nature de ces archives spécifiques comme un « espace » d’autorité. Les questions posées par les archives électroniques comme un « espace virtuel » aussi bien que celles suscitées par la création et la gestion pratique de cette collection d’archives spécifique sont examinées. Pour ce faire, le texte fait un lien entres ces questions et les débats sur le postmodernisme et les archives, et sur la littérature – géographique et autre – sur la nature du savoir situé (« situated knowledge »).